(untitled) ("Conference on Universal Science Research 2023", 2023)
"Stylistic Analysis of Poems" This comprehensive stylistic analysis delves into the literary techniques employed in a collection of poems. Through a systematic examination of various elements, including phonetic devices, symbolism, imagery, metre, rhythm, and figurative language, this study aims to unravel the intricate stylistic choices made by the poet. It explores how these stylistic devices contribute to the overall meaning, mood, and emotional resonance of the poems. By closely examining the poem’s structure, this analysis provides insights into how line breaks, stanza patterns, and rhythmic patterns enhance the flow and impact of the verses. The study also investigates the deliberate use of phonetic devices, such as alliteration, assonance, and rhyme, to create musicality and add emphasis to certain words or phrases.